D-mannose-Coating of Maghemite Nanoparticles Improved Labeling of Neural Stem Cells and Allowed Their Visualization by ex vivo MRI after Transplantation in the Mouse Brain. Issue 5 (May 2019) - Pongrac, Igor M.; Radmilović, Marina Dobrivojević; Ahmed, Lada Brkić; Mlinarić, Hrvoje; Regul, Jan; Škokić, Siniša; Babič, Michal; Horák, Daniel; Hoehn, Mathias; Gajović, Srećko
Magnetic resonance imaging (MRI) of superparamagnetic iron oxide-labeled cells can be used as a non-invasive technique to track stem cells after transplantation. The aim of this study was to (1) evaluate labeling efficiency of D-mannose-coated maghemite nanoparticles (D-mannose(γ-Fe2 O3 )) in neural stem cells (NSCs) in comparison to the uncoated nanoparticles, (2) assess nanoparticle utilization as MRI contrast agent to visualize NSCs transplanted into the mouse brain, and (3) test nanoparticle biocompatibility. D-mannose(γ-Fe2 O3 ) labeled the NSCs better than the uncoated nanoparticles. The labeled cells were visualized by ex vivo MRI and their localization subsequently confirmed on histological sections. Although the progenitor properties and differentiation of the NSCs were not affected by labeling, subtle effects on stem cells could be detected depending on dose increase, including changes in cell proliferation, viability, and neurosphere diameter. D-mannose coating of maghemite nanoparticles improved NSC labeling and allowed for NSC tracking by ex vivo MRI in the mouse brain, but further analysis of the eventual side effects might be necessary before translation to the clinic.